Theory of in-plane current induced spin torque in metal/ferromagnet bilayers. (20th April 2018) - Sakanashi, Kohei; Sigrist, Manfred; Chen, Wei
Abstract: Using a semiclassical approach that simultaneously incorporates the spin Hall effect (SHE), spin diffusion, quantum well states, and interface spin–orbit coupling (SOC), we address the interplay of these mechanisms as the origin of the spin–orbit torque (SOT) induced by in-plane currents, as observed in the normal metal/ferromagnetic metal bilayer thin films. Focusing on the bilayers with a ferromagnet much thinner than its spin diffusion length, such as Pt/Co with  ̃10 nm thickness, our approach addresses simultaneously the two contributions to the SOT, namely the spin-transfer torque (SHE-STT) due to SHE-induced spin injection, and the inverse spin Galvanic effect spin–orbit torque (ISGE-SOT) due to SOC-induced spin accumulation. The SOC produces an effective magnetic field at the interface, hence it modifies the angular momentum conservation expected for the SHE-STT. The SHE-induced spin voltage and the interface spin current are mutually dependent and, hence, are solved in a self-consistent manner. The result suggests that the SHE-STT and ISGE-SOT are of the same order of magnitude, and the spin transport mediated by the quantum well states may be an important mechanism for the experimentally observed rapid variation of the SOT with respect to the thickness of the ferromagnet.